2007
DOI: 10.1093/qjmed/hcm089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nesiritide on renal function in patients admitted for decompensated heart failure

Abstract: We failed to detect any significant risk of WRF in patients treated with nesiritide compared to conventional therapy in patients with decompensated HF during index hospitalization. Larger randomized, placebo-controlled trials are required to further elucidate the effect of nesiritide on renal function in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
2
18
1
Order By: Relevance
“…In another study, patients with decompensated heart failure who received nesiritide did not have an increased risk of deteriorating renal function compared to those who received only conventional therapy. [11] In this study the findings were unchanged, regardless of the definition of deterioration of renal function (rise in serum creatinine ≥0.3 mg/dl from baseline, with final creatinine level >1.5 mg/dl at day 3 of hospitalization, rise of serum creatinine ≥0.5 mg/dl, rise of serum creatinine ≥0.3 mg/dl anytime during hospitalization). Furthermore, nesiritide had a neutral effect on renal function in patients with decompensated congestive heart failure and mild chronic renal insufficiency.…”
Section: Impact Of Nesiritide On Renal Functioncontrasting
confidence: 56%
“…In another study, patients with decompensated heart failure who received nesiritide did not have an increased risk of deteriorating renal function compared to those who received only conventional therapy. [11] In this study the findings were unchanged, regardless of the definition of deterioration of renal function (rise in serum creatinine ≥0.3 mg/dl from baseline, with final creatinine level >1.5 mg/dl at day 3 of hospitalization, rise of serum creatinine ≥0.5 mg/dl, rise of serum creatinine ≥0.3 mg/dl anytime during hospitalization). Furthermore, nesiritide had a neutral effect on renal function in patients with decompensated congestive heart failure and mild chronic renal insufficiency.…”
Section: Impact Of Nesiritide On Renal Functioncontrasting
confidence: 56%
“…More recent studies found no significant difference among low-dose dopamine, low-dose nesiritide and placebo in improving clinical outcomes in AHF patients with renal dysfunction. [39-41]…”
Section: Resultsmentioning
confidence: 99%
“…B-type natriuretic peptide (BNP) binds to the A-type natriuretic peptide receptor presented on the surface of vascular smooth muscle and endothelial cells (6), resulting in activation of guanylate cyclase and the subsequent accumulation of intracellular cyclic GMP in target tissues (10), which can mediate natriuretic, diuretic and smooth muscle relaxant effects. It can inhibit the renin-angiotensinaldosterone system and the sympathetic nervous system (7,8), thus decreasing in systemic vascular resistance and cardiac preload and afterload by venous and arterial vasodilation and prevent myocardial remodeling and fibrosis, which results in increasing in cardiac output (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…B-type natriuretic peptide (BNP), one of the neuro-humor factors that produced and released from the ventricles that plays an important role in heart failure (6). With the in-depth study of the pathogenesis of heart failure in recent years, the functions of BNP have been further researched that not only does it have effects of diuretic and natriuretic, but it also can prevent myocardial remodeling and fibrosis through the side secretory pathway and inhibit the activation of renin-angiotensin-aldosterone system (RAAS) which can reduce both heart and renal function (7,8).…”
Section: Introductionmentioning
confidence: 99%